2018
DOI: 10.1063/1.5011362
|View full text |Cite
|
Sign up to set email alerts
|

Deep-level traps in lightly Si-doped n-GaN on free-standing m-oriented GaN substrates

Abstract: In this study, we investigated the deep-level traps in Si-doped GaN epitaxial layers by metal-organic chemical vapor deposition on c-oriented and m-oriented free-standing GaN substrates. The c-oriented and m-oriented epitaxial layers, grown at a temperature of 1000 °C and V/III ratio of 1000, contained carbon atomic concentrations of 1.7×1016 and 4.0×1015 cm–3, respectively. A hole trap was observed at about 0.89 eV above the valence band maximum by minority carrier transient spectroscopy. The trap concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…The possible physical origin of the trap T1 at EC -0.18 eV is the nitrogen-vacancy (VN) [34,35]. The deep-level trap T2 at EC -0.56 eV can be attributed to the nitrogen antisite (NGa)-related defect [36,37] in the n-type homoepitaxial GaN layer.…”
Section: Interface States and Deep-level Trapsmentioning
confidence: 99%
“…The possible physical origin of the trap T1 at EC -0.18 eV is the nitrogen-vacancy (VN) [34,35]. The deep-level trap T2 at EC -0.56 eV can be attributed to the nitrogen antisite (NGa)-related defect [36,37] in the n-type homoepitaxial GaN layer.…”
Section: Interface States and Deep-level Trapsmentioning
confidence: 99%
“…[45,46,[53][54][55] Several studies found those traps not only to be associated with carbon but also with the yellow luminescence around 2.2 eV. [47,[56][57][58] 2.1.1. Yellow Luminescence and the C N Acceptor Level: YL1…”
Section: Luminescence Of Single Carbon Defectsmentioning
confidence: 99%
“…[101] Based on the early GGA and LDA-predicted shallow C N acceptor level, blue luminescence bands in C-doped GaN are sometimes proposed to originate from DAP-type transitions between the C Ga donor level and the C N acceptor level. [46,57,88,98,103,104] Regarding the considerably deeper nature of the C N acceptor level derived by state-of-the-art first-principles calculations (see Section 2.1), this attribution should be revised. The luminescence band around 3.0 eV detected in GaN grown by MOCVD and HVPE might be associated with the C N À H irelated BL2.…”
Section: High C Concentration: Carbon On Ga Site -C Gamentioning
confidence: 99%
“…For the trap parameters, the energy level below the conduction band and the capture cross section were fixed at 0.6 eV and 5.0 × 10 −15 cm 2 for all GaN layers and the substrate, respectively [36]. Approximately 0.6 eV for the trap's energy level is a common value for the experimental results and is observed for the GaN grown on not only SiC but also GaN substrates [8,9,27,[36][37][38][39][40]. The trap concentration of the channel layer was fixed to be at as low as 1.0 × 10 15 cm −3 [37].…”
Section: Device Structures Of Gan Hemts On Gan Substratesmentioning
confidence: 99%